2016
DOI: 10.1002/14651858.cd002200.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up strategies for patients treated for non-metastatic colorectal cancer

Abstract: Follow-up strategies for patients treated for non-metastatic colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
156
1
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(171 citation statements)
references
References 85 publications
3
156
1
4
Order By: Relevance
“…Interestingly, although multiple follow-up regimens have been suggested in literature with differences in both frequency of follow-up and components used at various time points, the intensity and components of the follow-up are still a matter of debate [7,8]. A recent systematic review concluded that intensive follow-up strategies were associated neither with improved cancer-specific survival, nor with a higher detection rate for tumour recurrences after curative treatment of CRC [9].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, although multiple follow-up regimens have been suggested in literature with differences in both frequency of follow-up and components used at various time points, the intensity and components of the follow-up are still a matter of debate [7,8]. A recent systematic review concluded that intensive follow-up strategies were associated neither with improved cancer-specific survival, nor with a higher detection rate for tumour recurrences after curative treatment of CRC [9].…”
Section: Introductionmentioning
confidence: 99%
“…Two randomized control studies and a Cochrane meta-analysis of patients with colorectal cancer demonstrated no OS benefit with a more stringent follow-up protocol including thoracic cross-sectional imaging after surgery [19-21]. Nevertheless, recent recommendations on post-treatment surveillance of resected GEP-NENs based on the risk stratification of established prognostic factors allow for a more individualized, patient-tailored approach [22].…”
Section: Discussionmentioning
confidence: 99%
“…Trois méta-analyses ont montré une amélioration de la survie avec une surveillance « plus intensive » [2,4,37]. Ces trois méta-analyses se recoupent puisqu'elles regroupent à chaque fois quatre des principaux essais de surveillance publiés [3,[38][39][40].…”
Section: Recherche D'une Récidive Locale Ou Métastatiqueunclassified
“…Ces trois méta-analyses se recoupent puisqu'elles regroupent à chaque fois quatre des principaux essais de surveillance publiés [3,[38][39][40]. Il n'est donc pas étonnant que leurs résultats soient concordants, montrant qu'une surveillance intensive était associée à une réduction significative d'environ 20 % de la mortalité et à un diagnostic de récidive avancé sans toutefois de différence sur le nombre absolu de rechutes comme souligné dans l'étude néozélandaise [2].…”
Section: Recherche D'une Récidive Locale Ou Métastatiqueunclassified